Ethnomathematical exploration of the Al-Akbar National Mosque Surabaya in picture pattern material for fourth grade elementary mathematics - Muhammad Alfan Khoirush Shidqi; Via Yustitia (Universitas Sarjanawiyata Tamansiswa, 2024)
The Al-Akbar National Mosque in Surabaya was constructed with various forms of buildings and ornaments where ethnomathematics can be studied, particularly for drawing pattern material in fourth-grade elementary school. The objectives of this study are to describe: (1) the ethnomathematical links in the architecture of the Al-Akbar National Mosque, Surabaya, and (2) the material of image patterns for fourth-grade elementary school found in parts of the Al-Akbar National Mosque. This research utilizes qualitative methods with an ethnographic approach and was conducted at the Al-Akbar National Mosque in the Pagesangan area of Surabaya City. The objects studied include parts of the buildings and decorations of the Al-Akbar Mosque. Data collection methods included observation, interviews, and documentation. The results of the study show that (1) the Al-Akbar National Mosque has ethnomathematical relationships evident in its architecture, layout, and decorations. The concept of image patterns at the Al-Akbar National Mosque is found in the main dome, both outer and inner, as well as the outer pyramid dome. These structures demonstrate the concept of enlarged and smaller image patterns. (2) There are mathematical concepts, especially the pattern of enlarging and shrinking images, present in the Al-Akbar National Mosque, Surabaya. In conclusion, this study underscores the significance of ethnomathematics in architectural design and its potential educational applications in elementary school settings.